Modern opportunities of therapeutic treatment of allergic conjunctivitis. A review - D. Yu. Maychuk (Oftalʹmologiâ)
H1‑receptor antagonists are drugs of choice to treat allergy. They work very fast as their therapeutic effect develops within 10‑15 min, have good tolerability and almost no adverse side-effects, and require no frequent instillations. Levocabastine quickly inhibits allergic reaction caused by specific allergen or histamine. Levocabastine while being a highly-selective H1‑receptor antagonist is the most perspective topical mono-drug used to treat acute allergic conjunctivitis. Levocabastine applied on a spot produces instant effect which persists for a long time so that instillations twice a day (BID) are enough. Levocabastine is more effective than other 15 antihistamines. In contrast to previous antihistamines, levocabastine blocks vasodilatation and reduces vascular permeability increase. Levocabastine eye drops have good tolerability comparable with cromoglicic acid eye drops and placebo. Levocabas tine is successfully used in allergic conjunctivitis (pollinosis, perennial, vernal, rhinoconjunctivitis) treatment in children. Its efficacy is the same or even higher than that of cromoglycate and azelastine. 20 clinical studies (more than 1200 patients) revealed that levocabastine eye drops are effective, work quickly and have good tolerability. This drug is efficient in allergic conjunctivitis treatment and acute infectious conjunctivitis complex therapy.